Who Is Part of the “Mindset Context”? The Unique Roles of Perceived Professor and Peer Mindsets in Undergraduate Engineering Students’ Motivation and Belonging - Muenks, Katherine; Yan, Veronica X.; Telang, Nina K. (Frontiers in Education, 2021)
In the current study, we explore the unique roles that perceived professor and peer beliefs play in creating a mindset context for undergraduate engineering students. We found that students (N = 304) perceived their peers, as compared to their professors, to endorse stronger fixed beliefs about intelligence and more negative beliefs about effort and failure, what we refer to as “unproductive mindsets”. Students’ perceptions of their professors’ unproductive mindsets negatively predicted their motivation (utility, attainment, and intrinsic value of engineering) and sense of belonging, even controlling for students’ own mindsets. Further, students’ perceptions of their peers’ unproductive mindsets negatively predicted their motivation (intrinsic value and mastery goals), sense of belonging, and choice of a difficult assignment, even controlling for students’ own mindsets and their perceptions of their professors’ unproductive mindsets. These results suggest that when considering the mindsets that permeate academic contexts, it is important to consider the unique role of perceptions of both teachers (professors) and peers.